The Initiative of a Large Eurasian Partnership is a New Approach to the Formation of International Relations within a Single Continent Based on Established International Legal Norms and Rules - M. A. Eskindarov; V. V. Perskaya (Мир новой экономики, 2018)
The initiative of the big Eurasian partnership as a new format for the development of interstate interaction in the conditions of multipolarity within the existing legal norms and rules adopted by the international community in the period after the Second World War is analyzed; This form of partnership is based on the equality of interaction and sovereignty of each actor of international relations, excludes the formation of bloc thinking and the search / formation of the image of a potential enemy as a driving force of development and the obligatory consolidation of efforts against it around one or a group of countries; The authors point out that practically all the necessary institutions and mechanisms for the continuity of the implementation of this initiative have already been created, including ensuring international security and the sovereignty of every actor in international relations; At the same time, the authors emphasize the growing real resistance to the actual implementation of this partnership on the part of the US and the EU as proponents of monopolarism, incl. through propaganda and knowingly false information, the creation of explosive foci around the participating countries, fomenting the already existing historical contradictions between countries2 to direct interference in internal processes on the basis of the already deployed network of non-governmental organizations and the impact on the educational process.